Exploring employees' perceptions of their capability and success of sharing knowledge : implications for human resource management (HRM) : a dissertation presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Human Resource Management (HRM) at Massey University, Palmerston North, New Zealand - Abdul Jalal, Hayati (Massey University, 2012)
This thesis considers the relationships among knowledge sharing capability, organisational culture, and knowledge sharing success using employees’ perceptions. By exploring these relationships, the thesis seeks to help HRM become a more robust tool for successful employee knowledge sharing within organisations. Human attributes, incorporating employee perceptions of ability, motivation and opportunity to share, describe the construct “knowledge sharing capability”. The six perceptions of organisational cultural values examined include collaboration, innovativeness, formalisation, autonomy, expertise, and trust. Data were collected from knowledge workers of four MSC status Malaysian-owned Information Technology (IT) organisations in two states of Malaysia. Using random sampling, 500 questionnaires were distributed to employees at all levels of these organisations. Of these, 270 questionnaires were useful for data analysis, a 52% valid response rate. The results of factor analyses, however, showed the emergence of unanticipated combinations of organisational culture questionnaire items. This resulted in the emergence of four new cultural values (i.e. formal collaboration, trustworthiness, expertise, and independence). Correlations and multiple regressions were employed to address the proposed research questions. The results confirmed that: 1) knowledge sharing capability has a positive and significant relationship with knowledge sharing success; 2) knowledge sharing capability has a significant relationship with organisational culture; 3) organisational culture (as found in perceived values of formal collaboration, trustworthiness, and expertise) has a positive and significant relationship with knowledge sharing success; 4) perceived cultural values of formal collaboration, trustworthiness, and expertise perfectly mediated the relationship between knowledge sharing capability and knowledge sharing success; and 5) perceived cultural values of expertise and independence did Abstract ii | P a g e moderate the causal link of knowledge sharing capability and knowledge sharing success, but an increase in independence for employees’ capability reduces the success of knowledge sharing. The results suggest the importance of incorporating human attributes (that translate into capability to share knowledge) and organisational culture into the design of HRM practices. The outcome of re-orientating HRM practices to reflect cultural values so that knowledge sharing success is enhanced would be a valuable future investigation. These results show that the greatest potential for knowledge sharing success can be achieved when cultural values are integrated into HRM practices which are then implemented efficiently.
Keywords: Organisational learning; Corporate culture; Employees; Knowledge management